Electrochemically activated NiSe-NixSy hybrid nanorods as efficient electrocatalysts for oxygen evolution reaction. (1st December 2016) - Li, Xiao; Yan, Kai-Li; Rao, Yi; Dong, Bin; Shang, Xiao; Han, Guan-Qun; Chi, Jing-Qi; Hu, Wen-Hui; Liu, Yan-Ru; Chai, Yong-Ming; Liu, Chen-Guang
Graphical abstract: Highlights: Novel electrochemically activated NiSe-Nix Sy hybrid nanorods have been fabricated. The electrochemical activation can produce amorphous Ni(OH)2 layer on NiSe-Nix Sy . Ni(OH)2 can be easily transferred into NiOOH as actually active sites for OER. Activated NiSe-Nix Sy hybrid nanorods possess the enhanced OER performances. Abstract: Novel activated NiSe-Nix Sy hybrid nanorods have been fabricated by a facile electrochemical pre-activation process in alkaline solution as efficient electrocatalyts for oxygen evolution reaction (OER). The electrochemical pre-activation process facilitates the growth of an amorphous Ni(OH)2 layer on the surface of NiSe-Nix Sy hybrid nanorods, and Ni(OH)2 can be easily transferred into NiOOH in alkaline solution as actually active sites for OER. The chemical composition, oxidation state, hybrid structure and surface morphology of NiSe/NF, NiSe-Nix Sy /NF and activated NiSe-Nix Sy /NF have been characterized and confirmed by XRD, XPS, SEM, EDX and EDX mapping. Electrochemical measurements have revealed enhanced OER performances of activated NiSe-Nix Sy /NF including smaller overpotential, Tafel plot and charge-transfer resistance than NiSe/NF and NiSe-Nix Sy /NF. The superior OER performances of activated NiSe-Nix Sy electrocatalysts may be not only due to the hybrid nanorods but also ascribed to Ni(OH)2 layer on the nanorods derived from electrochemical pre-activation process. Therefore, the method of combining an electrochemical pre-activation process with novel hybrid nanostructures may be a feasible strategy for preparing excellent OER eletrocatalysts.